Accelerating CO2 capture of highly permeable polymer through incorporating highly selective hollow zeolite imidazolate framework. Issue 2 (8th October 2019) - Wu, Xingyu; Ren, Yanxiong; Sui, Guomin; Wang, Guangzhe; Xu, Guangshuai; Yang, Leixin; Wu, Yingzhen; He, Guangwei; Nasir, Nayab; Wu, Hong; Jiang, Zhongyi
Abstract: The implementation of high‐performance membranes in large‐scale CO2 capture has the potential to significantly decrease the capture cost and reduce the environmental footprints. However, highly permeable polymers rarely have sufficient selectivity for energy‐efficient carbon capture. In this study, zeolite imidazolate framework hollow nanoparticles (ZIF‐HNPs) were synthesized and embedded into highly permeable polymers as versatile fillers to prepare mixed matrix membranes (MMMs). The interior hollow architecture minimizes transport resistance of gas diffusion through the fillers while its molecular‐sieving shell provides high selectivity. With 28 vol% loading of ZIF‐HNPs, the membrane exhibits CO2 permeability of 7, 128 Barrer and CO2 /CH4 selectivity of 16.4 (57.7% and 31.4% higher than these of pristine membrane), which surpass the upper bound of the state‐of‐the‐art reported polymeric membranes. Meanwhile, we proposed a modified Maxwell model based on the hierarchical structure of the MMM to analyze the effects of cavity size and loading on gas transport behaviors within membranes.